Numerical evaluation of low-grade producer gas flow and combustion characteristics in swirl combustor - Chai Yik Zhien; K.A. Al-attab; Ibrahim I. Enagi; Abdul Rahman Mohamed; Irfan Anjum Badruddin; Sarfaraz Kamangar; M. Ahmed Ali Baig (Case Studies in Thermal Engineering)
Low-grade gas produced from waste biomass fuels is getting more attention as an additional heat source for boilers to cope with the rising constraints on carbon footprint. However, the main challenge is to achieve complete combustion of the gas with acceptable burner outlet temperature while maintaining simple and compact burner. Computational fluid dynamics was utilized to understand the hydrodynamic flow characteristics and combustion in the vane swirler geometry used in boilers. Low-grade producer gas from wood air-gasification was modeled and compared to pure syngas. The results are validated with experimental data and the accuracy of this work is ascertained. The effect of the combustion equivalence ratio and the different geometry parameters of swirl burner on flow and combustion characteristics were investigated. Elevation of swirl number at higher angles affected the mixing quality positively. Lean combustion at φ of 0.67 resulted in a significant drop in CO emissions down to around 1 ppm but with a considerable drop in chamber outlet temperature. On the other hand, stoichiometric combustion condition resulted in the highest temperature of 1891K while maintaining acceptable CO emissions of 47 ppm which represented the optimum operating condition. The best combustor geometry design was 1000 mm length, 150 mm diameter and 60o swirler angle.